A CuMgFe LDH catalytic membrane and its application in degradation of sulfonamide antibiotics
Through in-situ self-assembly and vacuum suction filtration technology, CuMgFe LDH is uniformly dispersed in membrane pores, which solves the problem of poor active site coverage and stability of LDH catalytic membrane, and achieves efficient removal of sulfonamide antibiotics, improving the stability of the catalytic membrane and Anti-pollution, reducing treatment costs.
Patent Information
- Application Number
- CN202310320207.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-27
Smart Images

Figure HDA0004151573070000011 
Figure HDA0004151573070000012 
Figure HDA0004151573070000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental catalysis, and in particular to a method for preparing a CuMgFeLDH catalytic membrane for degrading sulfonamide antibiotics. Background Art
[0002] Sulfonamide antibiotics are broad-spectrum antibiotics, mainly used to treat bacterial infections, prevent animal diseases and promote body growth. It is difficult for trace amounts of antibiotics to decompose in the water environment, which will cause a certain degree of harm to aquatic organisms, humans and microorganisms. Long-term drinking of water containing sulfonamide antibiotics will lead to decreased immunity. At the same time, the human kidneys will also suffer a certain degree of damage, and even cause "tri-toxic effects". In addition, in order to resist sulfonamide antibiotics, microorganisms mutate and produce antibiotic resistance genes (ARGs). The presence of drug-resistant bacteria (ARB) will lead to a decrease in the function of antibiotics in disease prevention and treatment, indirectly affecting human health. At the same time, the large-scale growth and reproduction of resistant bacteria will cause unpredictable harm to the safety of the entire environment and ecosystem. Sulfonamide antibiotic wastewater has a high COD content, complex composition, high chroma, large pH fluctuations, high treatment cost, and difficulty in treatment. It contains substances that are difficult for microorganisms to biodegrade, and has an inhibitory effect on microorganisms at a certain concentration. Therefore, it is particularly important and imperative to explore a new, efficient and green antibiotic treatment technology.
[0003] Persulfate-based advanced oxidation technology (SR-AOPs) and membrane coupling technology have become a highly efficient treatment technology for the degradation of sulfonamide antibiotic wastewater. Among them, layered double hydroxide (LDH) has received increasing attention in SR-AOPs due to its advantages such as abundant active sites and structural adjustability. LDH particles are evenly and tightly dispersed in the membrane pores and on the membrane surface to prepare a catalytic membrane. LDH not only provides electrons for the activation of PMS, but also inhibits the agglomeration of catalyst particles. In addition, LDH is anchored in the restricted membrane pores. Due to the tortuous path of the membrane pores, pollutants can be efficiently concentrated and converted, which enhances the mass transfer efficiency and thus improves the catalytic efficiency.
[0004] At present, the preparation methods of LDH catalytic membranes are mainly concentrated in the co-phase conversion method and the vacuum filtration method. The co-phase conversion method is to incorporate LDH into the polymer for preparing the membrane, but the preparation method using this method will cause some of the active sites of LDH to be covered in the process, reducing the catalytic effect. The vacuum filtration technology is used to deposit simple LDH on the membrane. Due to the weak interaction between the inorganic and organic membranes, the stability of the catalytic membrane is poor. In order to solve the above problems, the present invention utilizes the in-situ self-assembly and vacuum filtration combined technology to prepare the CuMgFe LDH catalytic membrane, and a low-cost and highly adhesive surface modifier is applied between the inorganic catalyst and the organic membrane, and then the LDH is evenly and tightly dispersed in the membrane pores by the vacuum filtration technology. This surface modifier can not only increase the interaction between the organic membrane and LDH, enhance the stability of the catalytic membrane, but also has hydrophilicity, and also improves the anti-pollution property of the membrane. The CuMgFe LDH catalytic membrane prepared by the present invention can effectively expose more active sites of LDH, has good stability and anti-pollution property, and can efficiently remove sulfonamide antibiotics. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a catalytic membrane by combining in-situ self-assembly and vacuum filtration. The CuMgFe LDH catalytic membrane prepared by the present invention has many exposed active sites, high PMS utilization rate, high efficiency in degrading sulfonamide antibiotics, and the CuMgFe LDH is evenly dispersed and has good stability, and can efficiently degrade sulfonamide antibiotics.
[0006] The present invention is achieved through the following technical solutions.
[0007] The present invention provides a CuMgFe LDH catalyst membrane, and the CuMgFe LDH catalyst membrane is prepared according to the following method:
[0008] (1) After the polysulfone membrane is soaked in deionized water for 12 to 24 hours, one side of the membrane is treated with a buffer solution of polyphenol compounds at pH = 8.1 to 8.6 (preferably pH 8.5), polymerized at room temperature for 1 to 3 hours (preferably 1 hour), and washed with water to obtain a polyphenol-treated polysulfone membrane; the buffer solution of polyphenol compounds is obtained by dissolving polyphenol compounds in a buffer solution at pH = 8.1 to 8.6, and the concentration of polyphenol compounds in the buffer solution of polyphenol compounds is 1-3 g / L (preferably 2 g / L); the preferred polymerization time of the present invention is 1 to 3 hours, and a time exceeding this time will significantly reduce the permeation flux of the membrane. If the membrane is directly soaked in the buffer solution of polyphenol compounds, it will be difficult for the solution to pass through the membrane.
[0009] (2) uniformly dispersing CuMgFe LDH in an ethanol aqueous solution to obtain a CuMgFe LDH dispersion; depositing the CuMgFe LDH in the CuMgFe LDH dispersion onto the polyphenol surface of the polyphenol-treated polysulfone membrane in step (1) by suction filtration, and drying to obtain a CuMgFe LDH catalytic membrane; the mass of the CuMgFe LDH is 0.4-1.4 mg / cm based on the area of the polyphenol surface of the polyphenol-treated polysulfone membrane. 2 (Preferably 1.2 mg / cm 2 ).
[0010] CuMgFe LDH tends to aggregate in pure water, so it needs to be dispersed in ethanol aqueous solution.
[0011] In one embodiment of the present invention, the CuMgFe LDH in step (1) is prepared as follows:
[0012] Cu 2+ Soluble inorganic salts, Mg 2+ Soluble inorganic salts, Fe 3+ The soluble inorganic salts are mixed and dissolved in water at a molar ratio of 3:1 to 4:2 to obtain a solution A; NaOH and Na2CO3 are mixed and dissolved in water at a molar ratio of 3:1 to obtain a solution B; the solution A and the solution B are simultaneously added dropwise to water C at a temperature of 30°C under stirring, and the pH is controlled to be 10.5±0.2; after the solution A is added, stirring is continued for at least 30 minutes, and then aged at 40°C for 24 hours. After the obtained reaction solution is cooled to room temperature, centrifuged, the obtained precipitate is washed with deionized water until neutral, and dried to obtain CuMgFe LDH (particles); in the solution A, Cu 2+ The concentration of soluble inorganic salts is 0.3 mol / L, Mg 2+ The concentration of soluble inorganic salts is 0.3 mol / L, Fe 3 + The concentration of the soluble inorganic salt is 0.2 mol / L; the volume ratio of the solution A to the water C is 1:2; in the solution B, the concentration of NaOH is 3 mol / L, and the concentration of Na2CO3 is 1 mol / L.
[0013] In one embodiment of the present invention, the Cu 2+ The soluble inorganic salt is copper sulfate pentahydrate (CuSO4·5H2O), and the Mg 2+ The soluble inorganic salt is magnesium sulfate heptahydrate (MgSO4·7H2O), and the Fe 3+ The soluble inorganic salt is ferric nitrate nonahydrate (Fe(NO3)3·9H2O).
[0014] Furthermore, in the solution A, the concentration of CuSO4·5H2O is 0.3 mol / L, the concentration of MgSO4·7H2O is 0.3 mol / L, and the concentration of Fe(NO3)3·9H2O is 0.2 mol / L.
[0015] In one embodiment of the present invention, the single-side treatment in step (1) is performed by first fixing the membrane in a mold, and then pouring a buffer solution of polyphenol compounds into the mold to immerse the upward side.
[0016] Furthermore, in step (1), the polyphenol compound contained in the buffer solution of polyphenol compounds is one or a mixture of two or more of dopamine, gallic acid, and tannic acid, preferably dopamine.
[0017] Furthermore, in step (1), the buffer salt in the buffer solution of the polyphenol compound is tris-HCl.
[0018] Furthermore, the volume of the ethanol aqueous solution in step (2) is 0.67 mL / mg based on the mass of the CuMgFe LDH.
[0019] The concentration of the ethanol aqueous solution in step (2) is based on sufficient uniform dispersion, and the present invention recommends a volume fraction of 10%-30%.
[0020] The CuMgFe LDH catalytic membrane prepared by the invention has good stability and high-efficiency catalytic activity.
[0021] The present invention also provides application of the CuMgFe LDH catalytic membrane in degrading sulfonamide antibiotics.
[0022] In one embodiment of the present invention, the sulfonamide antibiotic is sulfamethoxazole (SMX) or sulfamethoxazole (SMZ).
[0023] In one embodiment of the present invention, the application is as follows: the CuMgFe LDH catalytic membrane is fixed on a flat membrane performance tester, and a 5 mg / L aqueous solution of sulfonamide antibiotics is maintained as a feed solution for 30 minutes at 0.4 MPa to make the membrane in a stable state and adsorption saturation state, and then a peroxymonosulfate (PMS) aqueous solution with a final concentration of 60 mg / L is added to the feed solution to start the degradation reaction.
[0024] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0025] 1. The present invention adopts a coprecipitation method to synthesize the CuMgFe LDH catalyst in one step, which overcomes the influence of the Jahn-Teller effect on the Cu(OH)6 octahedral structure, has high crystallinity and an obvious layered structure. At the same time, the present invention introduces a third cation into the binary LDH to improve the stability of LDH.
[0026] 2. The present invention adopts a method combining in-situ self-assembly and vacuum filtration to prepare the CuMgFe LDH catalytic membrane. The CuMgFe LDH is evenly and tightly anchored in the membrane air, exposing more active sites, thereby improving the stability and anti-pollution property of the catalytic membrane.
[0027] 3. The catalytic membrane prepared by the present invention is used to degrade sulfonamide antibiotics, which can efficiently degrade sulfonamide antibiotics, improve the mineralization of pollutants, reduce metal ion leaching during the catalytic process, and avoid secondary pollution problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 (a) is a scanning electron microscope (SEM) image of the CuMgFe LDH material in Example 1; (b) is a SEM image of the CuMgFeLDH catalyst film.
[0029] Figure 2 This is the X-ray diffraction (XRD) pattern of the CuMgFe LDH material in Example 1.
[0030] Figure 3 This is the infrared spectrum (FT-IR) of CuMgFe LDH in Example 1.
[0031] Figure 4 This is a diagram showing the effect of CuMgFe LDH catalytic membrane (LDHm) activating PMS to degrade SMX and SMZ under different conditions in Example 1.
[0032] Figure 5 This is a diagram showing the catalytic degradation effect of SMX in the presence of different capture agents in Example 1.
[0033] Figure 6 1 and 2 are electron paramagnetic resonance (EPR) spectra of different active substances in Example 1, (a) is the EPR spectra of hydroxyl radicals and sulfate radicals, and (b) is the EPR spectra of singlet oxygen. DETAILED DESCRIPTION
[0034] As mentioned above, in view of the shortcomings of the prior art, the inventor of this case proposed the technical solution of the present invention after long-term research and extensive practice, the main basis of which at least includes:
[0035] 1) The suitable usage ratio of the present invention is Cu 2+ Mg 2+, Fe 3+ CuMgFe LDH with good crystallinity was prepared, which had good catalytic effect and less metal ion leaching.
[0036] 2) The present invention adopts a method combining in-situ self-assembly and vacuum filtration to prepare the CuMgFe LDH catalytic membrane, which overcomes the problem of weak interaction between the inorganic catalyst and the organic membrane, alleviates the membrane pollution problem, and improves the mass transfer rate of the degraded pollutants.
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation cases. It should be understood that the specific embodiments described at this time are only used to explain the present invention and are not used to limit the present invention.
[0038] The present invention is further described below with reference to specific embodiments:
[0039] Example 1
[0040] (1) Preparation of CuMgFe LDH:
[0041] Copper sulfate (CuSO4·5H2O), magnesium sulfate heptahydrate (MgSO4·7H2O) and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) were dissolved in water to prepare solution A, wherein the concentration of CuSO4·5H2O was 0.3 mol / L, the concentration of MgSO4·7H2O was 0.3 mol / L, and the concentration of Fe(NO3)3·9H2O was 0.2 mol / L; sodium hydroxide (NaOH) and sodium carbonate (Na2CO3) were mixed and dissolved in water to prepare solution B, wherein the concentration of NaOH was 3 mol / L. / L, the concentration of Na2CO3 is 1 mol / L; at 30°C, solution A and solution B are simultaneously dropped into a beaker containing 100 ml of ultrapure water and stirred. During the titration process, solution B is used to adjust the pH in the beaker and the pH in the beaker is maintained at 10.5±0.2; after all 50 ml of solution A is titrated, it is stirred for 30 min and then aged at 40°C for 24 h; the obtained reaction solution is cooled to room temperature and centrifuged, and the obtained precipitate is washed with deionized water until the pH is neutral, centrifuged, dried in a vacuum oven at 60°C and collected to obtain CuMgFe LDH.
[0042] (2) Preparation of CuMgFe LDH Catalytic Film
[0043] A polysulfone (PSf) flat ultrafiltration membrane (50000Da, Zhongke Ruiyang Membrane Technology (Beijing) Co., Ltd.) was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; dopamine was dissolved in 20ml Tris-HCl buffer solution with a pH of 8.5 to prepare a dopamine solution, wherein the concentration of the dopamine solution was 2g / L, and it was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60min, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted dopamine (DA) on the surface, and then the prepared CuMgFe LDH was added to a 20ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was performed to make it evenly mixed, wherein the mass of CuMgFe LDH was 1.2mg / cm 2 (30 mg); the CuMgFe LDH dispersion was deposited onto the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0044] (3) The CuMgFe LDH catalytic membrane obtained in step (2) was subjected to a flux test experiment. The permeation flux of the membrane was tested using a flat membrane performance evaluation instrument for cross-flow filtration. At room temperature and an operating pressure of 0.4 MPa, ultrapure water was used for pre-pressing for at least 30 minutes before the test. After the membrane was in a stable state, the outlet volume of the ultrapure water permeate was recorded within a certain period of time, and the permeation flux of the membrane was calculated by the formula. The flux of the catalytic membrane prepared by the present invention is 80 L / m 2 ·h
[0045] (4) The CuMgFe LDH catalytic membrane prepared in step (2) was fixed on a flat membrane performance tester, and 5 mg / L 1L SMX or SMZ was used as a feed liquid for 30 min at 0.4 MPa to make the membrane in a stable state and adsorption saturation state, and then peroxymonosulfate (PMS) with a final concentration of 60 mg / L was added to the feed liquid to start the degradation reaction. At different reaction time intervals, 1 mL of the reaction liquid was taken from the system and filtered through a 0.22 μm polytetrafluoroethylene filter membrane. The concentration of sulfamethoxazole was detected at 275 nm using ultra-high performance liquid chromatography (chromatographic column: Waters T3 column; mobile phase: 1% glacial acetic acid: acetonitrile = 6:4; column temperature 30°C; flow rate 0.2 mL / min; injection volume 10 μL). Figure 4 It can be seen that the removal rates of sulfamethoxazole (SMX) and sulfadimethoxine (SMZ) by the CuMgFe LDH catalytic membrane activated PMS obtained in the present invention are 98% and 96% respectively.
[0046] Example 2
[0047] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0048] (2) Preparation of CuMgFe LDH Catalytic Film
[0049] A polysulfone (PSf) flat ultrafiltration membrane was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; dopamine was dissolved in 20 ml of Tris-HCl buffer solution with a pH of 8.5 to prepare a dopamine solution, wherein the concentration of the dopamine solution was 1 g / L, and the solution was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60 minutes, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and then the prepared CuMgFe LDH was added to a 20 ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was performed to make it evenly mixed, wherein the mass of CuMgFe L DH was 1.2 mg / cm 2 (30 mg); the CuMgFe LDH dispersion was deposited onto the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0050] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 65L / m 2 ·h
[0051] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ. The removal rates of SMX and SMZ were 93% and 92% respectively within 30 minutes.
[0052] Example 3
[0053] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0054] (2) Preparation of CuMgFe LDH Catalytic Film
[0055] A polysulfone (PSf) flat ultrafiltration membrane was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; dopamine was dissolved in 20 ml of Tris-HCl buffer solution with a pH of 8.5 to prepare a dopamine solution, wherein the concentration of the dopamine solution was 3 g / L, and the solution was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60 minutes, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and then the prepared CuMgFe LDH was added to a 20 ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was used to make it evenly mixed, wherein the mass of CuMgFe LDH was 1.2 mg / cm 2 (30 mg) to obtain a CuMgFe LDH dispersion; the CuMgFe LDH dispersion was deposited on the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0056] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 60L / m 2 ·h
[0057] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ, and the removal rates of SMX and SMZ were 92% and 90% respectively within 30 minutes.
[0058] Example 4
[0059] Preparation of PDA membrane
[0060] A polysulfone (PSf) (50,000 Da, produced by Zhongke Ruiyang Membrane Technology (Beijing) Co., Ltd.) flat ultrafiltration membrane was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; dopamine was dissolved in 20 ml of Tris-HCl buffer solution with a pH of 8.5 to prepare a dopamine solution, wherein the dopamine solution concentration was 2 g / L, and the solution was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60 minutes, then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and dried in an oven at 40°C to obtain a polydopamine (PDA) membrane.
[0061] According to the flux test experiment in step (3) of Example 1, the flux of the prepared PDA membrane is 100 L / m 2 ·h
[0062] According to step (4) in Example 1, the prepared PDA membrane was subjected to a degradation experiment of SMX and SMZ, and the removal rates of SMX and SMZ were 10% and 7% respectively within 30 minutes.
[0063] Example 5
[0064] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0065] (2) 30 mg of the CuMgFe LDH prepared in step (1) was added to a suspension system containing 60 mg / L of PMS to start degradation. Within 30 min, the removal rates of SMX and SMZ were 69% and 74%, respectively.
[0066] Example 6
[0067] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0068] (2) Preparation of CuMgFe LDH Catalytic Film
[0069] A polysulfone (PSf) flat ultrafiltration membrane (50000Da, Zhongke Ruiyang Membrane Technology (Beijing) Co., Ltd.) was used as the base membrane, cut into appropriate sizes and soaked in ultrapure water for 12 hours before use; the prepared CuMgFe LDH was added to a 20ml mixed solution of anhydrous ethanol and pure water in a volume ratio of 3:7, and ultrasonic dispersion was performed to make the mixture uniform, wherein the mass of CuMgFe LDH was 1.2mg / cm 2 (30 mg); the CuMgFe LDH dispersion was directly deposited onto the PSf membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0070] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 300 L / m 2 ·h
[0071] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ, and the removal rates of SMX and SMZ were 60% and 52% respectively within 30 minutes.
[0072] Example 7
[0073] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0074] (2) Preparation of CuMgFe LDH Catalytic Film
[0075] A polysulfone (PSf) flat ultrafiltration membrane was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; dopamine was dissolved in 20 ml of Tris-HCl buffer solution with a pH of 8.5 to prepare a dopamine solution, wherein the concentration of the dopamine solution was 2 g / L, and the solution was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60 minutes, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and then the prepared CuMgFe LDH was added to a 20 ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was used to mix them evenly, wherein the mass of CuMgFe LDH was 0.8 mg / cm 2 (20 mg); the CuMgFe LDH dispersion was deposited onto the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0076] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 72 L / m 2 ·h
[0077] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ, and the removal rates of SMX and SMZ were 70% and 62% respectively within 30 minutes.
[0078] Example 8
[0079] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0080] (2) Preparation of CuMgFe LDH Catalytic Film
[0081] A polysulfone (PSf) flat ultrafiltration membrane was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; dopamine was dissolved in 20 ml of Tris-HCl buffer solution with a pH of 8.5 to prepare a dopamine solution, wherein the concentration of the dopamine solution was 2 g / L, and the solution was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60 minutes, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and then the prepared CuMgFe LDH was added to a 20 ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was performed to make it evenly mixed, wherein the mass of CuMgFe LDH was 1.0 mg / cm 2 (25 mg); the CuMgFe LDH dispersion was deposited onto the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0082] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 72 L / m 2 ·h
[0083] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ, and the removal rates of SMX and SMZ were 83% and 82% respectively within 30 minutes.
[0084] Example 9
[0085] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0086] (2) Preparation of CuMgFe LDH Catalytic Film
[0087] A polysulfone (PSf) flat ultrafiltration membrane was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; dopamine was dissolved in 20 ml of Tris-HCl buffer solution with a pH of 8.5 to prepare a dopamine solution, wherein the concentration of the dopamine solution was 2 g / L, and it was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60 minutes, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and then the prepared CuMgFe LDH was added to a 20 ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was used to make it evenly mixed, wherein the mass of CuMgFe LDH was 1.4 mg / cm 2 (35 mg); the CuMgFe LDH dispersion was deposited onto the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0088] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 72 L / m 2 ·h
[0089] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ, and the removal rates of SMX and SMZ were 88% and 90% respectively within 30 minutes.
[0090] Example 10
[0091] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0092] (2) Preparation of CuMgFe LDH Catalytic Film
[0093] A polysulfone (PSf) flat ultrafiltration membrane (50000Da, produced by Zhongke Ruiyang Membrane Technology (Beijing) Co., Ltd.) was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; tannic acid was dissolved in 20ml of Tris-HCl buffer solution with a pH of 8.5 to prepare a tannic acid solution, wherein the concentration of the tannic acid solution was 2g / L, and it was quickly poured into the mold so that one side of the membrane was in contact with the dopamine solution, and self-polymerized at room temperature for 60min, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and then the prepared CuMgFe LDH was added to a 20ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was performed to make it evenly mixed, wherein the mass of CuMgFe LDH was 1.2mg / cm 2 (30 mg); the CuMgFe LDH dispersion was deposited onto the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0094] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 157 L / m 2 ·h
[0095] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ, and the removal rates of SMX and SMZ were 66% and 70% respectively within 30 minutes.
[0096] Embodiment 11
[0097] (1) CuMgFe LDH was synthesized according to the preparation method in Example 1.
[0098] (2) Preparation of CuMgFe LDH Catalytic Film
[0099] A polysulfone (PSf) flat ultrafiltration membrane (50000Da, produced by Zhongke Ruiyang Membrane Technology (Beijing) Co., Ltd.) was used as the base membrane, cut into a suitable size and fixed in a customized mold, and soaked in ultrapure water for 12 hours before use; gallic acid was dissolved in 20ml Tris-HCl buffer solution with a pH of 8.5 to prepare a gallic acid solution, wherein the concentration of the gallic acid solution was 2g / L, and it was quickly poured into the mold so that one side of the membrane was in contact with the gallic acid solution, and self-polymerized at room temperature for 60min, and then the membrane was taken out and rinsed with a large amount of ultrapure water to remove the unreacted DA on the surface, and then the prepared CuMgFe LDH was added to a 20ml mixed solution of anhydrous ethanol and pure water with a volume ratio of 3:7, and ultrasonic dispersion was used to make it evenly mixed, wherein the mass of CuMgFe LDH was 1.2mg / cm 2(30 mg); the CuMgFe LDH dispersion was deposited onto the DA-treated flat membrane using a vacuum filtration device and dried in an oven at 40°C to obtain a CuMgFe LDH catalytic membrane.
[0100] According to the flux test experiment in step (3) of Example 1, the flux of the prepared catalytic membrane is 157 L / m 2 ·h
[0101] According to step (4) in Example 1, the prepared catalytic membrane was subjected to degradation experiments of SMX and SMZ, and the removal rates of SMX and SMZ were 76% and 72% respectively within 30 minutes.
Claims
1. A CuMgFe LDH catalyst membrane, characterized in that The CuMgFe LDH catalytic membrane is prepared as follows: (1) After the polysulfone membrane is soaked in deionized water for 12 to 24 hours, one side of the membrane is treated with a buffer solution of polyphenol compounds with a pH of 8.1 to 8.6, polymerized at room temperature for 1 to 3 hours, and washed with water to obtain a polyphenol-treated polysulfone membrane; the buffer solution of polyphenol compounds is obtained by dissolving polyphenol compounds in a buffer solution with a pH of 8.1 to 8.6, the concentration of polyphenol compounds in the buffer solution of polyphenol compounds is 1 to 3 g / L, and the polyphenol compounds contained in the buffer solution of polyphenol compounds are one or a mixture of two or more of dopamine, gallic acid, and tannic acid; (2) uniformly dispersing CuMgFe LDH in an ethanol aqueous solution to obtain a CuMgFe LDH dispersion; depositing the CuMgFe LDH in the CuMgFe LDH dispersion onto the polyphenol surface of the polyphenol-treated polysulfone membrane in step (1) by suction filtration, and drying to obtain a CuMgFe LDH catalytic membrane; the mass of the CuMgFe LDH is 0.4-1.4 mg / cm based on the area of the polyphenol surface of the polyphenol-treated polysulfone membrane. 2 .
2. The CuMgFe LDH catalyst membrane according to claim 1, characterized in that The CuMgFe LDH in step (1) is prepared as follows: Cu 2+ Soluble inorganic salts, Mg 2+ Soluble inorganic salts, Fe 3+ The soluble inorganic salts are mixed and dissolved in water at a molar ratio of 3:1 to 4:2 to obtain solution A; NaOH and Na2CO3 are mixed and dissolved in water at a molar ratio of 3:1 to obtain solution B; solution A and solution B are simultaneously added dropwise to water C at a temperature of 30°C under stirring, and the pH is controlled to be 10.5±0.2; after the addition of solution A, stirring is continued for at least 30 minutes, and then aged at 40°C for 24 hours. After the obtained reaction solution is cooled to room temperature, centrifuged, and the obtained precipitate is washed with deionized water until neutral, and dried to obtain CuMgFe LDH; in the solution A, Cu 2+ The concentration of soluble inorganic salts is 0.3 mol / L, Mg 2+ The concentration of soluble inorganic salts is 0.3 mol / L, Fe 3+ The concentration of the soluble inorganic salt is 0.2 mol / L; the volume ratio of the solution A to the water C is 1:2; in the solution B, the concentration of NaOH is 3 mol / L, and the concentration of Na2CO3 is 1 mol / L.
3. The CuMgFe LDH catalyst membrane according to claim 1, characterized in that: In step (1), the polyphenol compound contained in the buffer solution of polyphenol compounds is dopamine.
4. The CuMgFe LDH catalyst membrane according to claim 1, characterized in that: In step (1), the buffer salt in the buffer solution of the polyphenol compound is tris-HCl.
5. The CuMgFe LDH catalyst membrane according to claim 1, characterized in that: The concentration of the polyphenolic compounds in the buffer solution of the polyphenolic compounds in step (1) is 2 g / L.
6. The CuMgFe LDH catalyst membrane according to claim 1, characterized in that: The volume of the ethanol aqueous solution in step (2) is 0.67 mL / mg based on the mass of the CuMgFe LDH.
7. The CuMgFe LDH catalyst membrane according to claim 1, characterized in that: The volume fraction of the ethanol aqueous solution in step (2) is 10%-30%.
8. Use of the CuMgFe LDH catalytic membrane as claimed in claim 1 in the degradation of sulfonamide antibiotics.
9. The use according to claim 8, characterized in that: The sulfonamide antibiotic is sulfamethoxazole or sulfamethoxazole.